A seamless capsule for cigarettes, a method of manufacture and an aerosol generating article
Patent Information
- Application Number
- CN202610909747.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]针对现有烟用无缝胶囊在外观表现单一、传统着色方式存在色泽不稳定的问题,本发明提供了一种烟用无缝胶囊、制备方法及气溶胶生成制品
[0015]根据本发明提供的一种烟用无缝胶囊、制备方法及气溶胶生成制品,通过将云母颗粒引入胶囊壳体,利用其对入射光的干涉、反射与折射作用,在胶囊表面形成柔和、典雅且富有层次感的珍珠光泽。该珠光效果不仅显著区别于传统单色或哑光胶囊,赋予产品高端、精致的外观质感,还能显著增强胶囊表面摩擦性能,提升应用过程中的定位稳定性;另外,相较于水溶性有机色素易在交联、水洗、高温干燥等制程中发生迁移、溶出或褪色,导致批次间颜色不一致的问题,本发明采用的云母颗粒以物理方式嵌入胶囊壳体,不依赖溶解扩散显色,其珠光色彩由无机金属氧化物薄膜结构决定,具有极高的化学惰性与热稳定性。因此,在整个生产工艺及后续存储使用过程中均保持色泽恒定,显著提升产品外观一致性与质量稳定性。
Smart Images

Figure CN122875157A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerosol generation technology, specifically to a seamless tobacco capsule, its preparation method, and an aerosol-generated product. Background Technology
[0002] Seamless tobacco capsules refer to crushable beads added to the filter rods of aerosol-generating products. These beads have a rubber shell as the wall material and encapsulate a core material containing aroma compounds. Currently, most core materials are oily, with a very small number being water-soluble. When the seamless tobacco capsule is crushed, it releases some of the aroma compounds. During inhalation, the temperature of the smoke increases the volatilization of these aroma compounds, which then enter the user's mouth, enhancing the user's sensory experience.
[0003] With the continuous upgrading of the consumer market, consumers' demand for seamless tobacco capsules has gradually evolved from the early single "fragrance function" to a "multi-sensory synergistic experience" encompassing olfaction, touch, and vision. Besides flavor selection and release efficiency, the capsule's appearance, texture, color, and even surface feel are increasingly becoming key factors influencing consumer preferences and brand perception. However, currently available seamless tobacco capsules mostly employ transparent, semi-transparent, or simple dyeing schemes. Traditional coloring methods, such as water-soluble food colorings, are prone to migration, dissolution, or fading during cross-linking, washing, or drying processes, leading to uneven coloring in the finished product. Furthermore, these methods may damage the capsule shell's integrity, affect its bursting performance, and even pose safety risks. Therefore, overcoming these technical problems and defects has become a key issue that needs to be addressed. Summary of the Invention
[0004] To address the issues of monotonous appearance and unstable color in existing seamless tobacco capsules and traditional coloring methods, this invention provides a seamless tobacco capsule, a preparation method, and an aerosol-generated product.
[0005] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: The first aspect of this application provides a seamless capsule for tobacco, including a shell and a core liquid enclosed by the shell. The shell includes mica particles, which form a micro-protrusion structure on the surface of the shell. The coefficient of friction of the shell surface is 0.159-0.180. Within the visible light range of 400~760nm, the reflectivity of the shell at a 45° incident angle is A% in the 15° direction and B% in the 45° direction, wherein A and B satisfy the relationship: 5≤AB≤30; And / or, the gloss of the housing measured at an incident angle of 60° is C GU, where C satisfies the relationship: 40≤C≤80.
[0006] Optionally, the particle size of the mica particles is d1, where 2000 mesh ≤ d1 ≤ 200 mesh.
[0007] Optionally, 1200≤d1≤600 mesh.
[0008] Optionally, the mica particles include one or more of the following: mica coated with titanium dioxide, mica coated with iron oxide, and mica co-coated with titanium dioxide and iron oxide.
[0009] Optionally, the shell further includes a gelling agent, a plasticizer, and a curing agent, and the shell comprises the following components by weight: 2-10 parts gelling agent, 0.1-5 parts plasticizer, 0.1-5 parts curing agent, and 0.1-1.5 parts mica particles.
[0010] Optionally, the gelling agent includes one or more of alginate, konjac gum, gum arabic, carrageenan, guar gum, pectin, agar, locust bean gum, and gellan gum; and / or, The plasticizer includes one or more of the following materials: maltitol, erythritol, sorbitol, polyethylene glycol, fructose syrup, propylene glycol, fructooligosaccharides, glycerol, triethyl citrate, etc.; and / or, The curing agent includes one or more of water-soluble monovalent metal cation salts or water-soluble divalent metal cation salts.
[0011] Optionally, the seamless capsule for cigarettes is a spherical capsule, and the particle size of the seamless capsule for cigarettes is d2, where 1mm≤d2≤5mm.
[0012] The second aspect of this application provides a method for preparing a seamless tobacco capsule, comprising the following steps: Obtain the core fluid; A shell liquid is prepared for forming the shell of the seamless tobacco capsule; the shell liquid includes mica particles. The shell liquid and the core liquid are dripped into the coolant to form a spherical capsule, thus obtaining a wet capsule in which the shell encapsulates the core liquid; The wet capsules are dried to obtain seamless tobacco capsules that have been dried and shaped.
[0013] Optionally, the mass concentration of the mica particles in the shell liquid is c, where 0.05% ≤ c ≤ 2.00%.
[0014] A third aspect of this application provides an aerosol generating article, comprising a smoke-generating section, a cooling section, a filtration section, and a seamless tobacco capsule, wherein the seamless tobacco capsule is the seamless tobacco capsule described above or a seamless tobacco capsule prepared by the preparation method described above, wherein the seamless tobacco capsule is disposed at least in one of the smoke-generating section, the cooling section, or the filtration section.
[0015] According to the present invention, a seamless tobacco capsule, its preparation method, and an aerosol-generated product are provided. By introducing mica particles into the capsule shell, the interference, reflection, and refraction of incident light are utilized to form a soft, elegant, and layered pearlescent luster on the capsule surface. This pearlescent effect not only significantly distinguishes it from traditional monochrome or matte capsules, giving the product a high-end and refined appearance, but also significantly enhances the surface friction performance of the capsule, improving positioning stability during application. Furthermore, compared to water-soluble organic pigments, which are prone to migration, dissolution, or fading during cross-linking, washing, and high-temperature drying processes, leading to batch-to-batch color inconsistencies, the mica particles used in this invention are physically embedded in the capsule shell, independent of dissolution and diffusion for color development. The pearlescent color is determined by the inorganic metal oxide film structure, exhibiting extremely high chemical inertness and thermal stability. Therefore, the color remains constant throughout the entire production process and subsequent storage and use, significantly improving product appearance consistency and quality stability. Attached Figure Description
[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a photograph of a plurality of seamless white cigarette capsules provided in an embodiment of the present invention; Figure 2 This is a physical image of a plurality of seamless gold cigarette capsules provided in an embodiment of the present invention; Figure 3 This is a physical image of a plurality of seamless red cigarette capsules provided in an embodiment of the present invention; Figure 4 This is a physical image of a single white seamless tobacco capsule provided in an embodiment of the present invention; Figure 5 This is a physical image of a single seamless gold cigarette capsule provided in an embodiment of the present invention; Figure 6 This is a physical image of a single seamless red cigarette capsule provided in an embodiment of the present invention; Detailed Implementation To make the technical problems solved, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0018] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.
[0019] like Figure 1-6 As shown, in some embodiments, this application provides a seamless capsule for tobacco, including a shell and a core liquid enclosed by the shell. The shell includes mica particles, which form a micro-protrusion structure on the surface of the shell. The coefficient of friction of the shell surface is 0.159-0.180.
[0020] Specifically, the coefficient of friction of the housing surface is any one value or a range of any two values from 0.159, 0.162, 0.165, 0.168, 0.171, 0.174, 0.177 or 0.180; in a preferred embodiment, the coefficient of friction of the housing surface is 0.165-0.174.
[0021] When the coefficient of friction of the shell surface is 0.159-0.180, it exhibits excellent pinch-breaking operability and internal positioning stability of the filter rod: consumers can obtain a moderate anti-slip feel and clear breaking feedback when applying force with their fingertips, making operation easy and less prone to slipping; at the same time, sufficient static friction is formed between the capsule and the filter rod bundle, effectively preventing axial displacement or detachment during transportation, storage, or smoking; when the coefficient of friction of the shell surface is less than 0.159, the capsule surface becomes too smooth, making it easy to slip when pinched with fingertips, making it difficult to concentrate force, resulting in difficulty in pinching or requiring repeated operation; at the same time, the adhesion between the capsule and the filter rod material is insufficient, making it easy to slide, shift, or even detach under vibration or airflow, affecting the consumer's user experience; when the coefficient of friction of the shell surface is greater than 0.180, the surface micro-convex structure becomes too prominent or the density is too high, significantly increasing the pinch-breaking resistance, requiring users to apply more pressure, resulting in a stiff operating feel and a decreased experience; in addition, excessive friction may scratch the inner wall of the filter rod during capsule insertion or cigarette rolling, compromising the seal.
[0022] This invention introduces mica particles into the capsule shell, utilizing their interference, reflection, and refraction of incident light to create a soft, elegant, and layered pearlescent luster on the capsule surface. This pearlescent effect not only significantly distinguishes it from traditional monochrome or matte capsules, giving the product a high-end and refined appearance, but also significantly enhances the surface friction properties of the capsule, improving positioning stability during application. Furthermore, compared to water-soluble organic pigments that are prone to migration, dissolution, or fading during cross-linking, washing, and high-temperature drying processes, leading to batch-to-batch color inconsistencies, the mica particles used in this invention are physically embedded in the capsule shell, independent of dissolution and diffusion for color development. Their pearlescent color is determined by the inorganic metal oxide film structure, exhibiting extremely high chemical inertness and thermal stability. Therefore, the color remains constant throughout the entire production process and subsequent storage and use, significantly improving product appearance consistency and quality stability.
[0023] like Figure 1-6 As shown, in some embodiments, in the visible light range of 400-760nm, the reflectivity of the housing at 15° direction is A% and the reflectivity at 45° direction is B% under 45° incident conditions, wherein A and B satisfy the relationship: 5≤AB≤30; Specifically, AB can be any one value or a range of any two values from 5, 10, 15, 20, 25 or 30; in a preferred embodiment, AB is 15-25.
[0024] When AB is between 5 and 30, the capsule exhibits good angle-dependent reflection characteristics, displaying a layered pearlescent effect as the viewing angle changes. When AB is less than 5, the difference in reflectivity between the capsule surface at 15° and 45° is small, the interference and reflection effects of mica particles on light cannot be effectively manifested, the pearlescent effect is weak, the capsule appearance is close to matte, and lacks a sense of layering. When AB is greater than 40, the difference in reflectivity of the capsule shell is too large, the angle-dependent reflection characteristics are too strong, resulting in drastic changes in gloss on the capsule appearance at different viewing angles, making the visual effect dazzling. Furthermore, due to the excessive amount of mica particles added, the mechanical properties of the capsule shell will be affected.
[0025] like Figure 1-6 As shown, in one embodiment, the gloss of the housing measured at an incident angle of 60° is CGU (Gloss Unit), where C satisfies the relationship: 40≤C≤80.
[0026] Specifically, the value of C is any one point or any two points from 40, 45, 50, 55, 60, 65, 70, 75, and 80; in a preferred embodiment, the value of C is 55-75.
[0027] When C is in the range of 40-80, the shell has good gloss at a 60° viewing angle, indicating that the mica particles have formed a uniform micro-convex structure on the shell surface, which has a good reflective effect on light and ensures the presentation of the pearlescent effect. When C is less than 40, the gloss of the shell surface is weak, the pearlescent effect is not significant, and the visual appeal is insufficient. When C is greater than 80, the shell surface is too bright, the pearlescent effect appears sharp and dazzling, and it lacks a soft and elegant texture.
[0028] In some embodiments, the particle size of the mica particles is d1, where 2000 ≤ d1 ≤ 200 mesh.
[0029] Specifically, the particle size of mica is any one value or a range of any two values from 2000 mesh, 1800 mesh, 1600 mesh, 1400 mesh, 1200 mesh, 1000 mesh, 800 mesh, 600 mesh, 400 mesh or 200 mesh.
[0030] When the mica particle size is 2000-200 mesh, the mica particles within this size range are evenly distributed on the capsule shell surface, forming a moderately high micro-convex structure. This effectively scatters and interferes with visible light, exhibiting a soft, full, and layered pearlescent luster, significantly improving the product's appearance and texture. Simultaneously, its size is sufficient to enhance the capsule surface roughness, keeping the coefficient of friction stably maintained within the ideal range of 0.159–0.180, balancing a good crushing feel with stable positioning within the filter rod, and maintaining good dispersibility and film integrity during preparation, avoiding shell defects. When the mica particle size is less than 2000 mesh, because... If the particles are too small, they cannot effectively generate multi-layered interference and reflection of light, resulting in a flat color similar to ordinary pigments, making it difficult to achieve a high-end pearlescent texture. At the same time, the insufficient height of the micro-convex structure limits the improvement of the surface friction coefficient. When the particle size of mica particles is greater than 200 mesh, on the one hand, it will cause the mica particles to be difficult to disperse in the adhesive, and they are prone to sedimentation or agglomeration. During the drop forming process, this will cause local stress concentration or uneven surface of the shell, affecting the roundness and wall thickness consistency of the capsule. On the other hand, excessively large particles will also form sharp or abrupt surface protrusions, which not only destroy the soft appearance of pearlescent but may also puncture or scratch the inner wall of the filter rod, affecting the sealing performance.
[0031] In some preferred embodiments, 1200 mesh ≤ d1 ≤ 600 mesh.
[0032] When the particle size of mica particles is between 1200 mesh and 600 mesh, it achieves the best balance between pearlescent visual effect and surface functional performance: mica particles within this particle size range can efficiently interfere, reflect, and scatter visible light, presenting a bright, uniform, and deep pearlescent luster, significantly enhancing the premium feel and brand recognition of the capsules; at the same time, the moderate particle size forms a dense and gently sloping micro-convex structure on the surface of the capsule shell, effectively increasing the surface friction coefficient to the ideal range of 0.159–0.180, ensuring a good squashable feel and positioning stability within the filter rod, while also exhibiting excellent dispersion stability in the adhesive system, making it less prone to sedimentation or agglomeration, which is beneficial for the continuity of the dripping process and the uniformity of the capsule appearance, thus taking into account aesthetic value, user experience, and feasibility for industrial production.
[0033] In some embodiments, the mica particles include one or more of the following: mica coated with titanium dioxide, mica coated with iron oxide, and mica co-coated with titanium dioxide and iron oxide.
[0034] The aforementioned coated mica particles are all food-grade pearlescent pigments. By depositing one or more layers of metal oxides on the surface of natural mica flakes, different shades of pearlescent effect, such as silver-white, golden yellow, reddish-brown, and rose gold, are produced using the principles of light interference and reflection. This not only meets the needs of tobacco capsules for color diversity and a high-end visual appeal, but also has good chemical stability, heat resistance, and safety, and is suitable for the relevant regulatory requirements for tobacco product contact materials.
[0035] In some embodiments, the shell further includes a gelling agent, a plasticizer, and a curing agent, and the shell comprises the following components by weight: 2-10 parts gelling agent, 0.1-5 parts plasticizer, 0.1-5 parts curing agent, and 0.1-1.5 parts mica particles.
[0036] Specifically, the number of parts of the gel is any value or a range of any two values, which may be 2, 3, 4, 5, 6, 7, 8, 9 or 10 parts; in a preferred embodiment, the number of parts of the gel is 4-8 parts.
[0037] Specifically, the amount of plasticizer is any value or a range of any two values selected from 0.1 parts, 0.8 parts, 1.5 parts, 2.2 parts, 2.9 parts, 3.6 parts, 4.3 parts, or 5 parts; in a preferred embodiment, the amount of plasticizer is 0.8-4.3 parts.
[0038] Specifically, the number of parts of the curing agent is any value or a range of any two values selected from 0.1 parts, 0.8 parts, 1.5 parts, 2.2 parts, 2.9 parts, 3.6 parts, 4.3 parts, or 5 parts; in a preferred embodiment, the number of parts of the curing agent is 0.8-4.3 parts.
[0039] Specifically, the number of mica particles is any value or a range of any two values selected from 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 part, 1.3 parts, or 1.5 parts; in a preferred embodiment, the number of mica particles is 0.3-1.3 parts.
[0040] In this application, when the various components of the shell meet the above-mentioned ranges, it exhibits excellent film-forming properties, mechanical strength, and functional synergy; the gelling agent provides a stable three-dimensional network structure, ensuring the complete molding of the capsule shell and uniform wall thickness; the plasticizer effectively regulates the shell's flexibility, preventing brittleness and optimizing the feel when crushed; the curing agent promotes the cross-linking reaction, improving the shell's moisture resistance and storage stability; and the appropriately added mica particles, without disrupting the continuity of the film, are uniformly embedded in the shell surface to form a micro-convex structure, giving the capsule a stable pearlescent visual effect and an ideal coefficient of friction of 0.159–0.180. The synergistic effect of the components within the above-mentioned proportions gives the capsule excellent appearance, handling performance, positioning stability, and suitability for industrial production; when the various components of the shell do not meet the above-mentioned ranges, the following problems will occur: When the amount of gelling agent is less than 2 parts: the viscosity of the gel is insufficient, making it difficult to form a complete and continuous capsule shell, and problems such as incomplete dripping, uneven wall thickness or cracking are likely to occur; when the amount of gelling agent is more than 10 parts, the gel film is too hard and brittle, the resistance to pinching is significantly increased, the user experience is reduced, and wrinkles or cracks are likely to occur during the drying process. If the plasticizer content is less than 0.1 parts, the shell will be too soft and brittle, and will easily break during transportation or squeezing; if the content is more than 5 parts, the shell will be too soft and the strength will be reduced, which may cause the capsule to deform and stick together in the filter rod, or even leak the core liquid, while also affecting the stability of the friction coefficient. If the curing agent content is less than 0.1 parts, the cross-linking is insufficient, the shell has poor water resistance, and it is easy to absorb moisture and soften in a high humidity environment, resulting in dimensional instability or premature cracking; if the content is more than 5 parts, the cross-linking is excessive, the shell becomes hard and brittle, which also worsens the crushing performance and may inhibit the orderly arrangement of mica particles on the surface, weakening the pearlescent effect. If the amount of mica particles is less than 0.1 parts, the pearlescent effect is weak, making it difficult to achieve the expected visual recognition and high-end texture. It also has limited effect on improving the surface friction coefficient and cannot effectively improve positioning stability. If the amount of mica particles is more than 1.5 parts, the particle concentration is too high, which makes it easy for the particles to agglomerate or settle in the adhesive, resulting in uneven roughness of the shell surface, local stress concentration, and defects such as micropores and cracks.
[0041] In summary, only when each component is strictly controlled within the weight range can the optimal balance in terms of appearance, mechanical properties, functional characteristics, and process feasibility of seamless tobacco capsules be achieved.
[0042] In some embodiments, the gelling agent includes one or more of alginate, konjac gum, gum arabic, carrageenan, guar gum, pectin, agar, locust bean gum, and gellan gum.
[0043] Using the above-mentioned materials as gelling agents can form a dense, continuous, and mechanically strong three-dimensional network structure in the aqueous phase, which is beneficial for the stable formation of droplets during the dripping process. After drying, it forms a seamless capsule shell with uniform wall thickness, smooth surface, and is not easily broken, ensuring effective encapsulation of the core liquid and long-term storage stability. Secondly, gum arabic, guar gum, konjac gum, etc. have both thickening and emulsifying functions, which can effectively improve the viscosity and suspension stability of the glue system, prevent micron-sized mica particles from settling or agglomerating during the preparation and dripping process, and ensure their uniform distribution in the shell, thereby achieving the consistency of the pearlescent effect and the controllability of the surface micro-convex structure.
[0044] In some embodiments, the plasticizer includes one or more of the following materials: maltitol, erythritol, sorbitol, polyethylene glycol, fructose syrup, propylene glycol, fructooligosaccharides, glycerol, triethyl citrate, etc.
[0045] The above-mentioned plasticizers have the effect of improving the viscosity and plasticity of the adhesive and the flexibility of the shell.
[0046] In some embodiments, the curing agent includes one or more of a water-soluble monovalent metal cation salt or a water-soluble divalent metal cation salt.
[0047] Water-soluble monovalent metal cation salts include one or more of sodium chloride, potassium nitrate, potassium chloride, sodium sulfate, potassium hydroxide, or sodium acetate; the use of the above-mentioned water-soluble monovalent metal cation salts can crosslink with the colloidal matrix, promote the gelation process of the colloidal matrix, and improve the shell strength.
[0048] In some embodiments, the water-soluble divalent metal cation salt includes one or more of magnesium carbonate, zinc sulfate, calcium chloride, ferrous sulfate, magnesium chloride, calcium nitrate, or calcium lactate; the use of the above-mentioned water-soluble divalent metal cation salt has the effect of promoting gel formation and improving gel strength and stability.
[0049] In some embodiments, the seamless capsule for tobacco is a spherical capsule, and the particle size of the seamless capsule for tobacco is d2, where 1mm≤d2≤5mm.
[0050] Specifically, the particle size of the seamless tobacco capsule is any value or a range of any two values selected from 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm or 5mm; in a preferred embodiment, the particle size of the seamless tobacco capsule is 1.5mm-4.5mm.
[0051] When the particle size of seamless tobacco capsules is 1-5mm, it provides a significant flavor release intensity and high processability. When the particle size of seamless tobacco capsules is less than 1mm, it leads to a significant increase in production difficulty and insufficient flavor loading; when the particle size of seamless tobacco capsules is greater than 5mm, it leads to an increased risk of capsule breakage and excessive flavor loading, resulting in an overly pungent flavor.
[0052] The second aspect of this application provides a method for preparing a seamless tobacco capsule, comprising the following steps: Obtain the core fluid; Prepare a shell liquid for forming the shell of a seamless tobacco capsule; the shell liquid includes mica particles; The shell fluid and core fluid are dripped into the coolant to form spherical capsules, resulting in a wet capsule with the shell encapsulating the core fluid; The wet capsules are dried to obtain seamless tobacco capsules that have been dried and shaped.
[0053] Specifically, (1) preparation of adhesive solution: add gelling agent, plasticizer and curing agent into deionized water and stir to disperse until there are no large clumps. Then heat to 95°C and continue stirring and heating for 3-5 hours until uniformly dissolved to form adhesive solution; add food-grade mica particles into deionized water and disperse at high speed to make mica suspension. Then add the suspension into the adhesive solution and mix evenly to ensure that the mica particles are uniformly suspended in the adhesive solution. Then keep warm and stand for 30-60 minutes to remove air bubbles and obtain the outer shell adhesive solution.
[0054] (2) Drop forming: The adhesive liquid and the core liquid are synchronously transported to the double-layer concentric dropper through a gear pump and dropped into the circulating coolant at a rate of 30 drops / s. Under the action of circulating shear and surface tension of the coolant, an independent shell-core structure capsule is formed, in which the outer shell encloses the core liquid. During the falling process, the outer shell adhesive liquid cools and solidifies rapidly to obtain a semi-finished wet capsule.
[0055] (3) Cross-linking enhancement: The semi-finished wet capsules were immersed in a 1.0% calcium chloride solution for 10 minutes for cross-linking enhancement.
[0056] (4) Washing to remove oil: The cross-linked wet capsules are washed with water by a spray device to remove the residual oil on the surface.
[0057] (5) Drying: The semi-finished wet capsules after washing are put into a rotary drum dryer for drying. After drying, seamless tobacco capsules with pearlescent effect are obtained.
[0058] Furthermore, in step 2, the mass ratio of shell liquid to core liquid is (2-6):(1-3), thereby ensuring that the capsule is well formed and that the outer layer of adhesive liquid uniformly embeds the inner core liquid. When the mass ratio of shell liquid to core liquid is less than 2:3, the capsule shell thickness will be too low and the overall strength will be insufficient, affecting the forming process and causing cracking or leakage. When the mass ratio of shell liquid to core liquid is greater than 6:1, the capsule shell thickness will be too high and the overall strength will be too great, making it difficult to break and release during aspiration, thus affecting the user experience.
[0059] This invention pre-prepares food-grade mica particles into a highly dispersible suspension and uniformly incorporates it into a glue system. Combined with a dripping-cooling-drying process, the mica particles are oriented and firmly embedded on the shell surface. The resulting capsules exhibit a soft, lustrous, and layered pearlescent sheen with excellent color consistency, free from mottled or fading phenomena, significantly enhancing the product's appearance and brand recognition. Furthermore, the micro-protrusion structure formed by the mica particles on the shell surface, combined with optimized shell thickness and mechanical properties, ensures that the capsule surface friction coefficient is stably maintained within the ideal range of 0.159–0.180. This method ensures both a moderately slip-resistant and tactile feel when the capsule is crushed by the consumer's fingertips, while also guaranteeing that the capsule is firmly positioned within the filter rod and is not easily displaced by vibration or airflow, thus balancing user experience and product reliability. Furthermore, after being reinforced by calcium chloride cross-linking, the shell possesses appropriate rigidity and toughness: it exhibits strong resistance to pressure and breakage under normal storage and transportation conditions; and it can rapidly rupture when subjected to normal finger pressure, with a measured average crushing force of 1.0–2.0 kgf, enabling immediate release of flavoring and avoiding extreme situations such as "unbreakable" or "easily self-ruptible." In summary, the seamless capsule preparation method for tobacco products provided in the second aspect of this application successfully achieves a unity of aesthetic value and functional performance through precise control of the shell-to-core mass ratio, scientific design of the adhesive formulation, optimization of the mica dispersion process, and key post-processing steps.
[0060] In some embodiments, the mass concentration of mica particles in the shell liquid is c, 0.05% ≤ c ≤ 2.00%.
[0061] Specifically, the mass concentration of mica particles in the shell liquid is any one value or a range of any two values from 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%.
[0062] When the mass concentration of mica particles in the shell liquid is 0.05%-2.00%, the pearlescent effect is significant, the surface microstructure is uniform, the frictional properties are moderate, and the capsule film integrity is good. When the mass concentration of mica particles in the shell liquid is less than 0.05%, the pearlescent effect is weak or even invisible. At the same time, due to the insufficient number of particles, an effective micro-protrusion structure cannot be formed on the capsule surface, resulting in an overly smooth surface and a low coefficient of friction. This makes it easy for consumers to break the capsule, causing it to slip, or for the capsule to slide or fall off in the filter rod, affecting the reliability of use. When the mass concentration of mica particles in the shell liquid is greater than 2.00%, it will cause the viscosity of the gel to increase abnormally and the fluidity to decrease. The mica particles are prone to agglomeration or sedimentation. In addition, excessive particles will interfere with the gel network structure, increasing the risk of micropores, cracks, or brittle fracture.
[0063] In a preferred embodiment, the mass concentration of mica particles in the shell liquid is 0.5%-1.5%, and more preferably, the mass concentration of mica particles in the shell liquid is 0.75%-1.25%.
[0064] In some embodiments, a third aspect of this application provides an aerosol generating article, including a smoke-generating section, a cooling section, a filtration section, and a seamless tobacco capsule, wherein the seamless tobacco capsule is the seamless tobacco capsule described above or a seamless tobacco capsule prepared by the preparation method described above, wherein the seamless tobacco capsule is provided in at least one of the smoke-generating section, the cooling section, or the filtration section.
[0065] Specifically, the cooling and filtration sections utilize filament-based filter rods, which are made from cellulose acetate tow or polypropylene through spinning, bundling, stretching, and crimping processes. At least one seamless tobacco capsule is embedded within the filter rod. When a user inhales the aerosol-generated product, squeezing the seamless capsule releases the flavoring substances within, enhancing the aroma. Simultaneously, due to its proximity to the heat source, this section not only promotes the volatilization of flavoring substances but also effectively removes harmful components from the smoke through the filter rod's filtration function, improving the user experience and safety of the aerosol-generated product.
[0066] The beneficial effects of the present invention will be further illustrated below with reference to the embodiments.
[0067] To make the inventive objectives, technical solutions, and beneficial effects of this invention clearer, the invention is further described in detail below with reference to embodiments. However, it should be understood that the embodiments of this invention are merely for illustrative purposes and not for limiting the invention, and the embodiments are not limited to those given in the specification. Materials not specified in the embodiments were prepared under conventional conditions or according to the conditions recommended by the material supplier.
[0068] Example 1 illustrates the seamless tobacco capsule and its preparation method disclosed in this invention.
[0069] Capsule preparation: 8 parts of gelling agent pectin, 3 parts of plasticizer maltitol, and 3 parts of curing agent sodium chloride were added to deionized water and stirred until no large clumps agglomerated. The mixture was then heated to 95°C and stirred continuously for 4 hours until uniformly dissolved. 1 part of titanium dioxide-coated mica particles were added to deionized water and dispersed at high speed to prepare a mica suspension. The suspension was then added to the adhesive solution and mixed evenly to ensure the mica particles were uniformly suspended in the adhesive solution. The mixture was then kept at a constant temperature for 30-60 minutes to remove air bubbles, yielding the outer shell adhesive solution. The adhesive solution and core solution were synchronously pumped to a double-layer concentric dripper via a gear pump and dripped into a circulating cooling liquid at a rate of 30 capsules / s to form a semi-finished wet capsule. The semi-finished wet capsule was immersed in a 1.0% calcium chloride solution for 10 minutes for cross-linking enhancement. After cross-linking, the wet capsule was washed with water using a spray device to remove residual grease from the surface. The washed semi-finished wet capsule was then placed in a rotary drum dryer for drying. After drying, a seamless tobacco capsule with a pearlescent effect was obtained.
[0070] Examples 2-10 and Comparative Examples 1-3 Examples 2-10 and Comparative Examples 1-3 are used to illustrate the seamless tobacco capsules and preparation method disclosed in this invention, including most of the operation steps in Example 1 above, except that the parameters in Table 1 are used.
[0071] Table 1 The seamless tobacco capsules prepared in the above embodiments and comparative examples were subjected to the following performance tests: 1. Capsule refractive index: To facilitate the evaluation of the pearlescent effect of the capsules, the refractive index of the finished capsules at 25℃ was measured using a WYA-2S Abbe refractometer.
[0072] 2. Core Liquid Retention Rate: To evaluate the encapsulation effect of the seamless capsules for pearlescent cigarettes, the core liquid retention rate of the samples was determined. The initial core liquid weight of the finished capsules was recorded. 200g of the sample was placed in a sealed bag and stored at room temperature for 30 days. After 30 days, the whole capsule was weighed and then broken. The remaining core liquid in the outer shell was washed away with anhydrous ethanol and dried. The outer shell weight was recorded. The difference between the two weights is the core liquid weight retained by the capsule. The core liquid retention rate was calculated by the difference in core liquid weight before and after storage.
[0073] 3. Capsule crushing force: The crushing force of seamless capsules for finished cigarettes was analyzed and tested using a texture analyzer TA-new plus. The capsule was placed on the test platform, and the probe was pressed down to crush the capsule. The capsule crushing force value measured by the sensor was recorded.
[0074] 4. Coefficient of friction of capsules: The surface friction coefficient and friction force of capsule samples were measured using an MXZ-01 friction coefficient tester with a special slide rail.
[0075] 5. Difference in light reflectance of capsule surface: Using a spectrophotometer, under light incident at 45°, the reflectance of the capsule at 15° and 45° is measured, and the difference in reflectance ΔR is calculated.
[0076] 6. Surface gloss of capsules: The gloss of capsules at an incident angle of 60° was measured using a spectrophotometer.
[0077] The above experiment was performed in triplicate for each sample, and the final results are expressed as "mean ± standard deviation".
[0078] The corresponding experimental results of the examples and comparative examples are shown in Table 2.
[0079] Table 2 Test Results Table 3 Test Results Comparing Examples 1 and 6-9, it can be seen that when the mica particle size is 200-2000 mesh, the capsule exhibits the best overall performance, with a refractive index of 1.53-1.68, a capsule breakage force of 1.58-1.94 kgf, a core liquid retention rate of 88.65%-98.4%, a gloss of 55.88-66.53 GU, and a reflectance difference of 11.50-18.53, indicating a good balance between optical performance and mechanical strength. When the particle size is greater than 200 mesh, although the gloss is acceptable, the refractive index is 1.48 and the core liquid retention rate is 62.50%, which are significantly reduced. Moreover, the capsule crushing force is relatively low at 1.35 kgf, indicating that coarse particles may lead to poor film density, affecting sealing and strength. When the mica particle size is less than 2000 mesh, the refractive index of the capsule is 1.49 and the gloss is 57.42 GU, which are significantly reduced. This indicates that fine particles will weaken the pearlescent effect and optical reflection properties of mica.
[0080] Comparing Examples 1-5, it can be seen that when the mica particle content is 0.1-1.5 parts, or when the mass concentration of mica particles in the shell liquid is 0.05%-2.00%, the capsule maintains a good refractive index and a breaking force >1.64 kgf, indicating high mechanical strength; and the core liquid retention rate is >96.38%, indicating excellent sealing performance, while also possessing high gloss. When the mica particle content is less than 0.1 parts, or when the mass concentration of mica particles in the shell liquid is less than 0.05%, the capsule's refractive index is 1.40 and its gloss is 40.64. The difference between GU and reflectivity was 5.23, both of which were low, indicating that the amount added was insufficient and could not form an effective optical reflective layer, resulting in poor visual effect. When the amount of mica particles was higher than 1.5 parts or when the mass concentration of mica particles in the shell liquid was greater than 2.00%, the capsule breakage force was 0.89 kgf and the core liquid retention rate was 86.81%, both of which decreased significantly. This indicates that excessive mica particles would destroy the continuity of the gel matrix, causing the capsule shell to become brittle and less dense.
[0081] Comparing Examples 1, 10, and 1-3, it can be seen that when mica particles are used, the capsule refractive index > 1.65, gloss > 66.53 GU, and reflectance difference > 18.53, which are not only high but also have excellent mechanical strength and sealing performance, resulting in the best overall effect. When mica particles are not used, the capsule gloss is 37.65 GU and reflectance difference is 2.90, both of which are low and lack a pearlescent effect. When mica powder is used, although the core liquid retention rate is high, the gloss is 36.57 GU and reflectance difference is 3.60, which are still very low and cannot provide the required decorative optical effect. When titanium dioxide is used, although it has a certain refractive index, its gloss is 39.94 GU and reflectance difference is 4.77, which are far lower than those of mica particles, indicating that simply using titanium dioxide cannot achieve the pearlescent shimmering effect unique to the mica particles of this application.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A seamless tobacco capsule, comprising a shell and a core liquid enclosed by the shell, characterized in that, The shell comprises mica particles, which form a micro-protrusion structure on the surface of the shell. The coefficient of friction of the shell surface is 0.159-0.
180. In the visible light range of 400~760nm, the reflectivity of the capsule shell at a 45° incident angle is A% in the 15° direction and B% in the 45° direction, where A and B satisfy the relationship: 5≤AB≤30; and / or, the gloss of the shell measured at a 60° incident angle is C GU, where C satisfies the relationship: 40≤C≤80.
2. The seamless tobacco capsule according to claim 1, characterized in that, The particle size of the mica particles is d1, where 2000 mesh ≤ d1 ≤ 200 mesh.
3. The seamless tobacco capsule according to claim 2, characterized in that, 1200 mesh ≤ d1 ≤ 600 mesh.
4. The seamless tobacco capsule according to claim 1, characterized in that, The mica particles include one or more of the following: mica coated with titanium dioxide, mica coated with iron oxide, and mica co-coated with titanium dioxide and iron oxide.
5. The seamless tobacco capsule according to claim 1, characterized in that, The shell also includes a gelling agent, a plasticizer, and a curing agent, and the shell comprises the following components by weight: 2-10 parts gelling agent, 0.1-5 parts plasticizer, 0.1-5 parts curing agent, and 0.1-1.5 parts mica particles.
6. The seamless tobacco capsule according to claim 5, characterized in that, The gelling agent includes one or more of the following: alginate, konjac gum, gum arabic, carrageenan, guar gum, pectin, agar, locust bean gum, and gellan gum; and / or, The plasticizer includes one or more of the following materials: maltitol, erythritol, sorbitol, polyethylene glycol, fructose syrup, propylene glycol, fructooligosaccharides, glycerol, triethyl citrate, etc.; and / or, The curing agent includes one or more of water-soluble monovalent metal cation salts or water-soluble divalent metal cation salts.
7. The seamless tobacco capsule according to claim 1, characterized in that, The seamless capsule for tobacco is a spherical capsule, and the particle size of the seamless capsule for tobacco is d2, where 1mm≤d2≤5mm.
8. A method for preparing a seamless tobacco capsule as described in any one of claims 1-7, characterized in that, Includes the following steps: Obtain the core fluid; A shell liquid is prepared for forming the shell of the seamless tobacco capsule; the shell liquid includes mica particles. The shell liquid and the core liquid are dripped into the coolant to form a spherical capsule, thus obtaining a wet capsule in which the shell encapsulates the core liquid; The wet capsules are dried to obtain seamless tobacco capsules that have been dried and shaped.
9. The method for preparing seamless tobacco capsules according to claim 8, characterized in that, The mass concentration of the mica particles in the shell liquid is c, where 0.05% ≤ c ≤ 2.00%.
10. An aerosol-generating product, comprising a smoke-generating section, a cooling section, a filtration section, and a seamless tobacco capsule, characterized in that, The seamless tobacco capsule is the seamless tobacco capsule according to any one of claims 1-7 or the seamless tobacco capsule prepared by the preparation method according to any one of claims 8-9, wherein the seamless tobacco capsule is at least disposed in one of the smoke generation section, the cooling section or the filtration section.